Effect of Antihypertensive Therapy on SCORE-Estimated Total Cardiovascular Risk: Results from an Open-Label, Multinational Investigation—The POWER Survey - Guy De Backer; Robert J. Petrella; Assen R. Goudev; Ghazi Ahmad Radaideh; Andrzej Rynkiewicz; Atul Pathak (International Journal of Hypertension)
Background. High blood pressure is a substantial risk factor for cardiovascular disease. Design & Methods. The Physicians' Observational Work on patient Education according to their vascular Risk (POWER) survey was an open-label investigation of eprosartan-based therapy (EBT) for control of high blood pressure in primary care centers in 16 countries. A prespecified element of this research was appraisal of the impact of EBT on estimated 10-year risk of a fatal cardiovascular event as determined by the Systematic Coronary Risk Evaluation (SCORE) model. Results. SCORE estimates of CVD risk were obtained at baseline from 12,718 patients in 15 countries (6504 men) and from 9577 patients at 6 months. During EBT mean (±SD) systolic/diastolic blood pressures declined from 160.2 ± 13.7/94.1 ± 9.1 mmHg to 134.5 ± 11.2/81.4 ± 7.4 mmHg. This was accompanied by a 38% reduction in mean SCORE-estimated CVD risk and an improvement in SCORE risk classification of one category or more in 3506 patients (36.6%). Conclusion. Experience in POWER affirms that (a) effective pharmacological control of blood pressure is feasible in the primary care setting and is accompanied by a reduction in total CVD risk and (b) the SCORE instrument is effective in this setting for the monitoring of total CVD risk.